Linking Ethical Leadership to Followers’ Knowledge Sharing: Mediating Role of Psychological Ownership and Moderating Role of Professional Commitment - Saeed, Imran; Khan, Jawad; Zada, Muhammad; Zada, Shagufta; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás (Frontiers in Psychology, 2022)
This study examined (a) the influence of ethical leadership on knowledge sharing, (b) the mediating role of psychological ownership, and (c) the moderating effect of professional commitment between ethical leadership (EL) and knowledge sharing (KS). Data were collected from 307 public listed Pakistani companies’ employees. Statistical analyses were performed by using SPSS Version 25 and AMOS version 22. The findings indicate a positive relationship between EL and KS behavior. Additionally, the impact of EL on KS was partially mediated by psychological ownership. Furthermore, professional commitment buffers the link between EL and KS. This study contributes to the body of knowledge in the field of leadership by confirming the role of ethics. The results show that ethical leaders develop employee attitudes (i.e., psychological ownership and professional commitment) that contribute to employee KS behavior. Ethical leaders create and encourage a learning culture to enhance organizational performance. This study adds to the little data on the positive impact of EL on listed company’s employees and addresses the gaps in previous studies on the role of EL in changing environments. In addition, professional commitment as a moderator has not been previously investigated with ethical leadership antecedents.